The Pahang and Kalimantan variant of nocturnally subperiodic form of Brugia Malayi (Nematoda:Filarioidea) the causative agent of filariasis. - CrSiti Utari CrSiti Utari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Backgound: the nocturnally subperiodic form of B.malayi has been reported as health problem both in East Pahang, Semenanjung, West Malaysia and Kakap, West Kalimantan, Indonesia. The filarial worm is transmitted mainly by the same mosquito vector ie Mansonia uniformis.Objectives: to detect any difference of microfilarial behavioral pattern in peripheral blood in East Pahang ang West Kalimantan endemic areas by statistically meta analysis on available data published by previous workers.Methods: using Aikat and Das formula of statistical analysis.Results: B.malayi' s microfilariae still tended to show nonperiodically in East Pahang and periodically already those found in West Kalimantan.Conclusion: nocturnally subperiodic form of B.malayi shows as different variant (subsubspecies) of those found in East Pahang, Malaysia and West Kalimantan, Indonesia. Key words: B. Ma/ayi's microfilaria - nocturnally subperiodic - nocturnally periodic - nonperiodic - metaanalysis